2021
DOI: 10.1002/fsn3.2422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bromelain on the quality of smoked salted duck

Abstract: Nowadays, many cured meat products are produced from different raw materials and under different processing conditions (Lorenzo et al., 2008;Toldra, 2006). During the processing of cured meat products, chemical and biochemical changes lead to produce a large number of volatile compounds which contribute to their characteristic flavor (Shi et al., 2021). Smoked salted duck is one of the Chinese traditional cured meat products which are largely favored by consumers in China due to its unique flavor (Li et al., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Using the bromelain enzyme's hydrolytic capabilities to generate flavoring compounds, some approaches have been performed by applying this enzyme directly to enhance the flavor of an entire piece of meat instead of using it as a substrate for obtaining isolated flavorings (Ye et al., 2021). In this case, authors tested smoked salted ducks with different bromelain dosages, and the results revealed, thanks to electronic tongue detection beyond other analysis, that there were significant improvements in the umami, saltiness, and richness of the whole smoked salted duck, but at the same time it was effectively assessed the reduction of the bitterness when applying 900 U/g of bromelain.…”
Section: Valorization and Potential Applications Of Pineapple And Pap...mentioning
confidence: 99%
“…Using the bromelain enzyme's hydrolytic capabilities to generate flavoring compounds, some approaches have been performed by applying this enzyme directly to enhance the flavor of an entire piece of meat instead of using it as a substrate for obtaining isolated flavorings (Ye et al., 2021). In this case, authors tested smoked salted ducks with different bromelain dosages, and the results revealed, thanks to electronic tongue detection beyond other analysis, that there were significant improvements in the umami, saltiness, and richness of the whole smoked salted duck, but at the same time it was effectively assessed the reduction of the bitterness when applying 900 U/g of bromelain.…”
Section: Valorization and Potential Applications Of Pineapple And Pap...mentioning
confidence: 99%